A global theory of justice for new governance : from process to substance with 'parity of participation' - Hermann, Martin (2014)
This thesis proposes a new counter-narrative to the neo-liberal agenda that combines two seemingly disparate bodies of work: New Governance and Nancy Fraser’s theory of justice. New Governance is a new and rapidly growing strand of legal thought and practi ce that has simultaneously developed a following in Europe and the United States. In short, legal scholars in this field of research are advocating a shift away from long-standing command-style, fixed-rule regulation toward more collaborative, bottom-up, and flexible modes of regulation.
Law
Keywords: FRASER; Nancy; neoliberal hegemony; new governance

Are markets everywhere? : Ludwig von Mises, Friedrich Hayek and Karl Polanyi - Rodigues, Joao (The University of Manchester, 2010)
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; MISES; Ludwig von

Sustainable Development and the North American Free Trade Agreement: A Polanyian Interpretation - Plante, David J (University of Utah, 2004)
Political Science
Keywords: economic integration; environment and development; environment and trade; environmental accounts and accounting; environmental equity; population growth; sustainability; sustainable development; thesis; trade and environment

Sustainable Agriculture in the United States and France: A Polanyian Perspective - Barham, Mary Elizabeth (2000)
Sociology
Keywords: France; social movements; sustainable agriculture